THE IMPLEMENTATION OF INTERTEXTUALITY APPROACH TO DEVELOP STUDENTS’ CRITI-CAL THINKING IN UNDERSTANDING LITERATURE - Arapa Efendi (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2012)
This paper promotes the teaching technique that can be used as a means of developing learners’ critical thinking in understanding literature. The promoted technique is conducted through the implementation of intertextuality approach that may require some supported materials; short stories, drama script, and poems as the exemplification materials in the EFL classroom. Keywords: Intertextuality approach, short stories, drama, literary texts.